The potential of diallyl trisulfide for cancer prevention and treatment, with mechanism insights - Lu, Ling; Gao, Zihan; Song, Jiajia; Jin, Longtao; Liang, Zhaofeng (Frontiers in Cell and Developmental Biology, 2024)
Cancer has become an important public health problem worldwide, and there is currently a lack of effective treatment and prevention strategies. Natural plant active ingredients have been proven to be a safe and highly promising method for preventing and treating cancer. It has been found that diallyl trisulfide have anticancer effects in multiple types of cancer via inhibiting cancer proliferation, enhancing chemotherapy sensitivity, inducing apoptosis/autophagy, suppressing invasion/migration, regulating microenvironment. With the deepening of research on new strategies for cancer prevention and treatment, the role of diallyl trisulfides in cancers occurrence, prognosis, and drug resistance is also receiving increasing attention. In order to better understand the relationship between diallyl trisulfides and various cancer, as well as the role and mechanism of diallyl trisulfides in cancer prevention and treatment, we briefly summarized the role and function of diallyl trisulfide in cancers.